The «Black Swans» of new liberalism - A. Kh. Denil′khanov (Проблемы постсоветского пространства)
The term «Black Swan», which is metaphorically used by the modern American scientist Nassim Nicholas Taleb in his theoretical research, means inexplicable randomness of events, their predictability and unpredictability for the expert, but the consequences of which are of great importance. In other words, these are important accidents that, according to N. Taleb, affect the result of the experiment and the course of history. In the Russian state there were many global events, each of which could be described as a «Black Swan». The article analyzes only two of them, which have occurred in modern history and have led to disastrous consequences for both Russia and the world, through the prism of the methodology of historical development and political discourse. The political and ideological platform of these events were the ideas of liberalism, the embodiment of which caused unforeseen, stochastic consequences, which became the object of this study. The author substantiates the conclusion that the intellectual part of the Russian society in the development of new concepts of political and state structure was guided by speculative theories and implemented mental schemes in the absence of real objective and subjective prerequisites, turning these processes into socio-political experiments. In the field of practical policy, according to the author, special attention should be paid to the factor of personal responsibility of actors in the development of political strategy and tactical decision-making.